Active P species in P-doped graphite carriers improving the electrocatalytic performance of supported Pt towards the hydrogen evolution reaction. (11th November 2021) - Li, Zekun; Han, Fei; Liu, Ziwu; Peng, Qiancheng; Wang, Quan-De; Sun, Maomao; Kang, Guo-Jun
Abstract : Experiments demonstrate that the prepared Pt@PDGs with ca. 6 wt% Pt display higher area and mass specific activities than 20 wt% Pt/C. Calculations reveal that the C–O–P with a pentagon defect improves the HER activity of loaded Pt dominantly. Abstract : To develop more efficient Pt-based catalysts towards the hydrogen evolution reaction (HER), in this work, phosphorus-doped graphite (PDG) with high HER activity was employed as the support of the Pt catalyst. Electrochemical tests demonstrated that the area and mass specific HER activities of the as-prepared Pt@PDG with ca. 6.0 wt% Pt were ca. 3.34–4.5 and 1.5–2.7 times those of the commercial 20 wt% Pt/C catalyst at −0.2 and −0.215 V in acidic and alkaline media. Correlations of Pt HER activity with P moieties indicated that the C–O–P played a dominant role in improving the HER performance of Pt compared to the other P species. Simulations revealed that the C–O–P with a pentagon-ring defect could change the charge and spin densities of Pt and increase the adsorption energy of loaded Pt greatly, which results in the HER-performance enhancement of supported Pt, providing a new insight for the development of high-performance Pt catalysts.